Education and science: current trends - Serebrennikova A. V., Goppe G. G., Kirgin D. S., Pokhomchikova E. O., Pogodaeva A. N., Baranov G. V., Khviiuzov M. A., Galashev A. N., Musina R. I., Danilchenko S. L., Rukina S. N., Amerzhanova Z. M., Isymov D. K., Kireeva E. V. (Education and science: current trends, 2017)
the author analyzes the issues related to the formation and development in the history of law and philosophy such thing as rights and freedoms of man and citizen. Human rights – one of the fundamental concepts of human civilization, it has played and continues to play the role of one of the vectors in the development of society. In a review of the opinion given on the discussion representatives of the world of philosophy and law from the inception of this concept to its current state.
Keywords: философия; понятие; право; law; philosophy; мировая культура; права и свободы человека и гражданина; World Culture; the concept of the rights and freedoms of man and citizen